Al-Ḥākim and the Dhimmīs - Walker, Paul E. (Medieval encounters, 2015)
Dhimmī (non-Muslim subjects, mostly Christians and Jews, who were afforded protection by the Islamic state) persecution in Islamic Egypt included most notably that instigated by the Fatimid caliph al-Ḥākim from about 395/1004 until near the end of his reign in 411/1021. This ruler imposed burdensome restrictions and sumptuary regulations on Jews and Christians, causing significant numbers of them to adopt Islam. He also commenced the state-sponsored destruction of churches and synagogues, most famously the Church of the Holy Sepulchre. And yet, near the end, this same caliph relented, mitigating the severity of his previous policies. A general picture of what happened already exists, but the precise chronological order of these events and many of the exact details remain vague. Most importantly, we continue not to have a reason for his radically new policy. Al-Maqrīzī’s various accounts provide useful evidence although they hardly suffice. The Jewish reaction is far from clear. Two Christian histories, those by the Melkite Yaḥyā ibn Saʿīd of Antioch and the History of the Patriarchs of Alexandria, confirm many particulars. However none of this information explains why. Was al-Ḥākim moved to act as he did in response to, or in imitation of, the strikingly similar set of restrictive regulations imposed long before under the so-called “Pact of ʿUmar”?